EXPLORING THE ROLE OF PHYSICAL EDUCATION IN ENHANCING MENTAL HEALTH AND WELL-BEING AMONG ADOLESCENTS: BACKGROUND AND RATIONALE - Shukla, Tushar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study investigates the impact of physical education (PE) on adolescent mental health and well-being, focusing on how varying levels of physical activity influence mental health outcomes. The research employs a mixed-methods design, combining quantitative data from surveys and qualitative insights from interviews and observations. Findings reveal that higher physical activity levels are associated with significantly lower General Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) scores, indicating reduced anxiety and depression, respectively. Additionally, students with higher physical activity levels reported higher self-esteem. Qualitative data highlight that activities promoting teamwork and social interaction in PE contribute to improved mental health. The study underscores the importance of diverse and engaging PE programs in fostering adolescent mental well-being and offers recommendations for enhancing PE curricula to better support mental health. Limitations include the cross-sectional nature of the study and reliance on self-reported data. Future research should explore longitudinal impacts and diverse populations.